LEARNING TO WRITE TEXT OF PERSUATION USING THE CIRCUIT LEARNING METHOD IN VIII MIDDLE SCHOOL STUDENTS - Mallma Fatimah Al Tanjung; Ika Mustika; Teti Sobari (IKIP Siliwangi, 2021)
Writing is an important activity for students to hone memory and perfect in learning activities and as a measurement tool for students who are creative in learning to write, especially persuasion texts. The purpose of this study 1). The activity of writing persuasive texts of the students before and after using the Circuit Learning method. 2) Knowing the student's performance when completing assignments to measure the ability to write persuasion texts. The author uses a population of class VIII junior high school students with a sample of 27 students. The research design used was a quasi-experimental method and the data technique used a pre-test and a final test. Tests in the form of tests of knowledge and skills test to write persuasion texts before and after using the Circuit Learning method. Based on the analysis and discussion, there are results of 1) Asymp.Sig. (2-tailed) has a value of 0.000 <0.05, so it can be accepted that it is accepted, meaning that there is a difference between the results of writing the persuasive text for the pretest and posttest so that it can state that